2014
DOI: 10.1227/neu.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

High Response Rates and Prolonged Survival in Patients With Corticotroph Pituitary Tumors and Refractory Cushing Disease From Capecitabine and Temozolomide (CAPTEM)

Abstract: This is the first report of prolonged antitumor response to and radiographic complete remissions as a result of CAPTEM in patients with aggressive pituitary tumors who had exhausted all other therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 32 publications
1
49
0
1
Order By: Relevance
“…In this patient, MGMT remained low. In other studies (25,105), MSH6, MLH1, MSH2 and PMS2 did not predict the effect of TMZ.…”
Section: -Dna Mismatch Repair (Mmr) Proteinsmentioning
confidence: 73%
See 1 more Smart Citation
“…In this patient, MGMT remained low. In other studies (25,105), MSH6, MLH1, MSH2 and PMS2 did not predict the effect of TMZ.…”
Section: -Dna Mismatch Repair (Mmr) Proteinsmentioning
confidence: 73%
“…A study using treatment with capecitabine before TMZ (CAPTEM) found a partial response of long duration in 4 out of 4 corticotroph tumours, of which one was a carcinoma (105). In studies with NET cell lines, the authors had observed a synergistic apoptosis when TMZ had been given after pretreatment with capecitabine compared with TMZ alone.…”
Section: Combination Of Tmz With Other Drugsmentioning
confidence: 99%
“…Approximately 20 corticotroph tumors have been treated with temozolomide in the literature, 3 of which were SCA carcinomas which did not maintain response to temozolomide [22,35,54]. One group reported use of a combined regimen of temozolomide and capecitabine in a patient with an SCA which did lead to a reduction in tumor size [65].…”
Section: Managementmentioning
confidence: 99%
“…Increased risk of secondary malignancies (particularly leukemia and lymphoma) has been reported with prolonged administration of alkylating agents such as TMZ. It is currently unclear which regimen offers the best efficacy and which is associated with a reduced risk of secondary malignancy [121], whereas there are no data to support whether TMZ can be used alone or in combination with other medications such as pasireotide or capecitabine [122,123,124]. …”
Section: Treatmentmentioning
confidence: 99%